(untitled) (Fiep Bulletin - online, 2014)
Work related diseases are becoming more worrying to companies’ managers, since they provoke temporary leaves causing losses to both companies and employees. Thus research is being done to minimize them. One of the possible solutions is to invest in programs that promote employees’ health and quality of life. Laboral gymnastics is one example, which is capable of tuning and fortifying muscular structures required for work and contributing to improving interpersonal relations reducing the incidence of osteomuscular diseases. This study aims to evaluate the level of improvement in the incidence of osteomuscular diseases, especially lombalgies after the implementation of a laboral gymnastic program. A sample of 52 male employees was selected from an engineering company. The data were measured from two questionnaires filled in by the subjects before and after the 6 month program. The values found were the average age of 32,5 0,57 and the average work period within the company was 32 2,04 months and a reduction of 20% in the incidence of lombalgies. The conclusion is that laboral gymnastics can be an effective means of preventing column related problems and rehabilitating individuals carrying lombalgies. Also it improves employees’ quality of life since it is a way to neutralize the negative effects of work and the inadequate use of technologies on the body